Production of serine chymotrypsin-like elastase by Aspergillus fumigatus strains - Guglielminetti, M.; Piccioni, P.; Iadarola, P.; Luisetti, M.; Caretta, G. (Boletín Micológico, 1993)
Thirty-four Aspergillus fumigatus strains isolated from air, horse-hair; agricultural soil and human samples were screened to evaluate the production of elastase. Aspergillus fumigatus strains were grown in elastin solid medium, showing a widespread elastin solubilization. However, isolates from human and agricultural soil samples were found to be the highest elastase producers. Then, eight out of 34 strains were grown in four different liquid media, on wich we investigated total and specific proteolytic activity. Results from this experiments suggest that the elastase production is induced by the presence of elastin as a substrate and that the elastase is a chymotrypsin like enzyme. Inhibitory profile showed that the A.fumigatus elastase is a serine proteinase.